The effects of barley particle size on finishing-pig performance - Robert D Goodband; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1986)
Two trials utilizing 280 finishing pigs were conducted to evaluate the effects of barley particle size on finishing-pig performance. In Experiment 1, pigs fed barley ground through a hammermill with a 1/8-in screen were not different in average daily gain (ADG) or feed efficiency (F/G) from pigs fed a milo-based diet ground through a 3/16-in screen. Pigs fed either 3/16 or 1/4-in ground barley grew slower and were less efficient (P<.02) than those fed either the milo or finely ground barley diet. Experiment 2 was conducted in a similar manner, with the exception that mill run barley was used instead of a specific variety. In Experiment 2, ADG and average daily feed intake (ADFI) were not different between dietary treatments. This response resulted in a trial x treatment interaction for these criteria. Results for feed efficiency were similar to those in Experiment 1; pigs fed 3/16 or 1/4-in ground barley diets were less efficient (P<.02) than those fed l/8-in ground barley or 3/16-in ground milo. These results suggest that the variety of barley is an important criteria in determining feeding value for finishing-pigs, and that reducing particle size of the diet by fine grinding improves feed efficiency.; Swine Day, Manhattan, KS, November 20, 1986
Keywords: Swine day; 1986; Kansas Agricultural Experiment Station contribution; no. 87-133-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 507; Swine; Barley; Finishing pig performance